Sintesa Surfaktan Ramah Lingkungan Metil Ester Sulfonat Dari Palm Oil Methyl Ester Dengan Variasi Kecepatan Pengadukan Dan Suhu Reaksi - Rahmad Agung Yanuardhi; Nirwana Nirwana; Irdoni HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Waste generated from surfactant LABS (Linear Alkylbenzene sulphonate) can be toxic to aquatic organisms, causing damage to ecosystems and groundwater that may havean impact on human life. Surfactants are surface active agent, which works to lower the surface tension of a liquid, active nature is derived from the dual nature of the molecule. Surfactants are molecules that have polar groups that like water(hydrophilic) and non-polar groups are like oil (lipophilic). Methyl Ester Sulfonate (MES) is one type of anionic surfactant which has advantages in terms of detergency, resistant to hardness, are renewable and environmentally friendly. Methyl EsterSulfonate produced by the process of sulfonation between Palm Oil Methyl Ester (POME) and sulfonating agent Sodium metabisulphite (Na2S2O5) with a catalyst of aluminum oxide (Al2O3). This research aims to create a methyl ester sulfonate withstirring speed variation and reaction temperature. Sulfonation process using Palm Oil Methyl Ester mole ratio of 1: 1.5 and sulfonating compounds with sodium metabisulfite variation stirring speed of 400, 450, 500 rpm and temperature variations of 80, 100,120 0C, with a reaction time of 4.5 hours. The results were obtained product category decrease in surface tension of water is a stirring speed of 400 rpm and a temperature of80 0C, with a decrease of 21 dyne / cm. for category decrease interfacial tension obtained the best product on the stirring speed of 450 rpm and a temperature of 100 0C, with a decrease of 5.80 dyne / cmKeyword : Anionic Surfactants, Methyl Ester, Methyl Ester Sulfonate, Sulfonation, Surfactant.